2005
DOI: 10.1093/molehr/gah207
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the epidermal growth factor system in human endometrium during the menstrual cycle

Abstract: The epidermal growth factor (EGF) system is ubiquitous in humans and plays fundamental roles in embryogenesis, development, proliferation and differentiation. As the endometrium of fertile women is characterized by proliferation and differentiation, we hypothesize a role for the EGF system. Fourteen premenopausal women had endometrial samples removed on day 6 +/- 1 and day 6 +/- 1 and 12 +/- 1 after ovulation during one menstrual cycle. RNA was extracted and analysed by real-time PCR, and immunohistochemistry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(77 citation statements)
references
References 30 publications
1
71
0
5
Order By: Relevance
“…In the present study, there was a significant increase in protein expression of EGFR at 50 days, a known player associated with cell proliferation in the uterus [11]. As mentioned above, studies in our lab have associated uterine proliferation with increased levels of EGFR [15,16].…”
Section: Egf Signalingsupporting
confidence: 70%
See 1 more Smart Citation
“…In the present study, there was a significant increase in protein expression of EGFR at 50 days, a known player associated with cell proliferation in the uterus [11]. As mentioned above, studies in our lab have associated uterine proliferation with increased levels of EGFR [15,16].…”
Section: Egf Signalingsupporting
confidence: 70%
“…One pathway containing tyrosine kinases that has been implicated in the regulation of uterine proliferation and apoptosis is the epidermal growth factor (EGF) pathway [11]. EGF and its receptors, the ErbB family of tyrosine kinases that includes epidermal growth factor receptor (EGFR), form a network that is known to play a role in cell proliferation in many tissue types.…”
Section: 378-tetrachlorodibenzo-p-dioxin (Tcdd)mentioning
confidence: 99%
“…In contrast, Ejskjaer et al were unable to detect EGF in endometrial samples [57]. This discrepancy may be due to different collection times in that Ejskjaer et al did not examine any samples during ovulation [55,57].…”
Section: Epidermal Growth Factormentioning
confidence: 96%
“…Studies have shown that EGF expression fluctuates during the menstrual cycle with expression highest during the late proliferative and secretory phases [55,56]. In contrast, Ejskjaer et al were unable to detect EGF in endometrial samples [57]. This discrepancy may be due to different collection times in that Ejskjaer et al did not examine any samples during ovulation [55,57].…”
Section: Epidermal Growth Factormentioning
confidence: 99%
“…EGFR, in endometrium, is localized to the basal part of surface epithelial cells, only in stromal cells, or both to epithelial and stromal cells [Bigsby et al, 1992;Wang et al, 1994;Imai et al, 1995;Möller et al, 2001;Ejskjaer et al, 2005]. It is primarily located to the cell membrane but also to the cytoplasm [Nyholm et al, 1993;Reinartz et al, 1994;Khalifa et al, 1994;Niikura et al, 1996;Ejskjaer et al, 2007].…”
Section: Expression and Clinical Significance Of Erbb Receptors In Enmentioning
confidence: 99%